IgG Fc variant cross-reactivity between human and rhesus macaque FcγRs. Issue 3 (3rd April 2017) - Boesch, Austin W.; Miles, Adam R.; Chan, Ying N.; Osei-Owusu, Nana Y.; Ackerman, Margaret E.
ABSTRACT: Non-human primate (NHP) studies are often an essential component of antibody development efforts before human trials. Because the efficacy or toxicity of candidate antibodies may depend on their interactions with Fcγ receptors (FcγR) and their resulting ability to induce FcγR-mediated effector functions such as antibody-dependent cell-meditated cytotoxicity and phagocytosis (ADCP), the evaluation of human IgG variants with modulated affinity toward human FcγR is becoming more prevalent in both infectious disease and oncology studies in NHP. Reliable translation of these results necessitates analysis of the cross-reactivity of these human Fc variants with NHP FcγR. We report evaluation of the binding affinities of a panel of human IgG subclasses, Fc amino acid point mutants and Fc glycosylation variants against the common allotypes of human and rhesus macaque FcγR by applying a high-throughput array-based surface plasmon resonance platform. The resulting data indicate that amino acid variation present in rhesus FcγRs can result in disrupted, matched, or even increased affinity of IgG Fc variants compared with human FcγR orthologs. These observations emphasize the importance of evaluating species cross-reactivity and developing an understanding of the potential limitations or suitability of representative in vitro and in vivo models before human clinical studies when either efficacy or toxicity may be associated with FcγR engagement.